Dihydromyricetin improves type 2 diabetes-induced cognitive impairment via suppressing oxidative stress and enhancing brain-derived neurotrophic factor-mediated neuroprotection in mice. (7th February 2018) - Ling, Hongyan; Zhu, Zemei; Yang, Jihua; He, Jianqin; Yang, Sisi; Wu, Di; Feng, Shuidong; Liao, Duanfang
Abstract: Type 2 diabetes mellitus (T2DM) leads to cognitive impairment (CI), but there have been no effective pharmacotherapies or drugs for cognitive dysfunction in T2DM. Dihydromyricetin (DHM) is a natural flavonoid compound extracted from the leaves of Ampelopsis grossedentata and has various pharmacological effects including anti-oxidant and anti-diabetes. Thus, we investigated the effects of DHM on CI in T2DM mouse model and its possible mechanism. To induce T2DM, mice were fed with high-sugar and high-fat diet for 8 weeks, followed by a low dose streptozotocin (STZ) administration. After the successful induction of T2DM mouse model, mice were treated respectively with equal volume of saline (T2DM group), 125 mg/kg/d DHM (L-DHM group), or 250 mg/kg/d DHM (H-DHM group). After 16 weeks of DHM administration, the body weight (BW), fasting blood glucose, blood lipids, intraperitoneal glucose tolerance (IPGT), and cognitive function were determined. Then, alterations in the expressions of oxidative stress markers and brain-derived neurotrophic factor (BDNF) in the hippocampus were investigated. Our findings demonstrated that DHM could significantly ameliorate CI and reverse aberrant glucose and lipid metabolism in T2DM mice, likely through the suppression of oxidative stress and enhancement of BDNF-mediated neuroprotection. In conclusion, our results suggest that DHM is a promising candidate for the treatment of T2DM-induced cognitive dysfunction.